HTLV-1 encephalitis. Issue 1 (30th August 2021) - King-Robson, Josh; Hampton, Timothy; Rosadas, Carolina; Taylor, Graham P; Stanton, Biba
Abstract : A 53-year-old woman developed subacute onset of upper limb weakness, sensory loss and cerebellar dysfunction. She was known to have human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy. MR scan of the brain showed extensive T2 hyperintensity within the deep and subcortical white matter, with punctate contrast enhancement. Cerebrospinal fluid (CSF) was lymphocytic with very high levels of HTLV-1 provirus in both CSF and peripheral blood lymphocytes. We diagnosed HTLV-1 encephalomyelitis and started high-dose methylprednisolone followed by a slow corticosteroid taper. She recovered well and regained functional independence in the upper limbs. Neurological manifestations of HTLV-1 infection extend beyond classical 'tropical spastic paraparesis' and are under-recognised. We review the literature on HTLV-1 encephalitis and discuss its diagnosis and management.